TOWARDS "UNITY IN DIVERSITY" IN EUROPEAN DEVELOPMENT AID THROUGH DONOR HARMONIZATION AND DECENTRALIZED COOPERATION? A CASE STUDY OF FLANDERS AND BELGIUM. (5th August 2013) - Waeterloos, Evert; Renard, Robrecht
SUMMARY Official donors have over the past decade pledged to enhance aid effectiveness by improving donor harmonization. To this effect, the European Union (EU) launched initiatives on a division of labor among its Member States. At the same time, the EU encourages Europe's subnational authorities to engage in their own development cooperation. This however seems to undermine the same harmonization effort. Belgium, characterized by multiple levels of government, illustrates that these two approaches to aid effectiveness—collective division of labor at the national level and decentralized cooperation at lower levels—are only partially compatible. In partner countries where both the federal Belgian and regional Flemish governments are active donors, Belgium's composite aid is poorly harmonized. A principal–agent framework helps to explain such selfish positioning. This article argues that a higher degree of complementarity and harmonization among Belgium's various authorities is feasible, albeit in forms that are specific to recipient country and context. As both donors are not so much competing in aid supply policies but rather in terms of supply management, such technical arguments may assist in lessening the political pressure to selfishly emphasize diversity over unity. Copyright © 2013 John Wiley & Sons, Ltd.